Degradacja mitu w literaturze fantasy - Trocha, Bogdan (1963- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the following research is the phenomenon of a myth degradationand its presence in fantasy literature. That means, the issues concerningrelationships between fantasy and a fairy tale, an epic poem and a legend willbe covered by phonological "epoche" focusing only on description of a myth, religioussymbol, a mythologem, and mythic metaphor in that literature.
Keywords: fantastyka; literatura; literaturoznawstwo